INDIKATOR ALAMI BERBASIS EKSTRAK DAUN ERPA (Aerva sanguinolenta) UNTUK DETEKSI BORAKS DALAM PRODUK PANGAN: Natural Indicator from Aerva sanguinolenta Leaf Extract for Borax Detection in Food Products - Triastuti, Desy; Aprilliani, Fenny; Dwi Ningrat, Fitri; Apriani, Farida (Jurnal Agroindustri Terapan Indonesia, 2025)
Aerva sanguinolenta leaves contain anthocyanis that can be utilized as a borax detector in food products. This study aimed to determine the charateristics of Aerva sanguinolenta leaf extract and evaluate its effectiveness as a natural color indicator for borax detection. The research employed a Completely Randomized Design (CRD) with four treatments of borax concentrations (0%, 1%, 2%, and 3%) with three replications. The paramaters observed included the yield and pH of the extract, as well as the reaction of the extract and the natural color indicator when exposed to varying borax concentration treatments. Data were analyzed using ANOVA and followed by DMRT at a 5% significance level. The result showed that the leaf extract yield was 79% with a pH of 4,93. The extract reacted positively to borax, producing varying color intensities across treatments. The natural color indicator reacted with borax and exhibitied significant differences (P<0,05) in red and yellow color parameters. The higher the borax concentration resulted in darker indicator color, indicating that natural color indicator from Aerva sanguinolenta leaves are effective for borax detection.